Faktor Risiko Lingkungan Dan Perilaku Yang Mempengaruhi Kejadian Kesakitan Malaria Di Propinsi Sumatera Selatan (Analisis Lanjut Data Riset Kesehatan Dasar 2007) - Akhmad Saikhu (ASPIRATOR - Journal of Vector-borne Disease Studies, 2011)
Abstracts. Malaria is a major public health problem in Indonesia, causing mortality not onlyfor infant and pregnant women but also decreasing productivity among workers. To provideimportant and up to date of health related information, National Institute of Health Researchand Development – MOH Republic of Indonesia had held National Baseline Health Research(Riskesdas) on 2007.The extended analysis of NHBR particularly on malaria has been conducted to evaluate distributionof malaria cases and its influencing risk factors especially the behavioral and environmentalfactor. This study found that there were associations between malaria cases withage (p<0.000), occupation (p<0.005), time consumed to seek health services (Posyandu),health services utilization (p<0.05), type of water sludge irrigation (p<0.001) and usage ofinsecticide-treated net (p<0.000). This study recommended the improvement environmentcondition and health education to improve knowledge, attitude, and practice; provide moreand better insecticide-treated mosquito bed net can be applied to solve the problems thatwere issued from the findings of the study. Extended malaria research should be conductedto provide better understanding of malaria control.